2021
DOI: 10.1590/1981-86372021002120190101
|View full text |Cite
|
Sign up to set email alerts
|

Association between Pell and Gregory classification and the difficulty of the extraction of the lower third parties

Abstract: Lower third molar extraction is a common procedure in Oral and Maxillofacial Surgeons routine. However, even though this procedure is frequent, sometimes its course is unexpected. In this scenario, some developed classifications help to predict the difficulty level for such extractions. Objective This study aimed to verify the association of Pell and Gregory classifications I and II and surgical difficulty through lower third molar extractions. Methods Voluntary patients from the Dentistry Course of the Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was suggested that with each millimeter increase in the red line measurement, surgical difficulty will increase three times, with a greater risk of inferior alveolar nerve injury [2]. Few clinical studies have investigated the effect of Winter's red line as an indicator of the depth of impaction [3][4][5] on the extraction difficulty of impacted teeth, as many studies used the position of impaction as per Pell and Gregory classification [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…It was suggested that with each millimeter increase in the red line measurement, surgical difficulty will increase three times, with a greater risk of inferior alveolar nerve injury [2]. Few clinical studies have investigated the effect of Winter's red line as an indicator of the depth of impaction [3][4][5] on the extraction difficulty of impacted teeth, as many studies used the position of impaction as per Pell and Gregory classification [6][7][8][9][10][11][12].…”
mentioning
confidence: 99%